ThX – a next-generation probe for the early detection of amyloid aggregates. Issue 18 (21st February 2020) - Needham, Lisa-Maria; Weber, Judith; Varela, Juan A.; Fyfe, James W. B.; Do, Dung T.; Xu, Catherine K.; Tutton, Luke; Cliffe, Rachel; Keenlyside, Benjamin; Klenerman, David; Dobson, Christopher M.; Hunter, Christopher A.; et al.
Abstract : Introducing ThX, a next-generation ThT derivative that allows for the early detection of amyloid aggregates at the bulk and single-aggregate levels. Abstract : Neurodegenerative diseases such as Alzheimer's and Parkinson's are associated with protein misfolding and aggregation. Recent studies suggest that the small, rare and heterogeneous oligomeric species, formed early on in the aggregation process, may be a source of cytotoxicity. Thioflavin T (ThT) is currently the gold-standard fluorescent probe for the study of amyloid proteins and aggregation processes. However, the poor photophysical and binding properties of ThT impairs the study of oligomers. To overcome this challenge, we have designed Thioflavin X, (ThX), a next-generation fluorescent probe which displays superior properties; including a 5-fold increase in brightness and 7-fold increase in binding affinity to amyloidogenic proteins. As an extrinsic dye, this can be used to study unique structural amyloid features both in bulk and on a single-aggregate level. Furthermore, ThX can be used as a super-resolution imaging probe in single-molecule localisation microscopy. Finally, the improved optical properties (extinction coefficient, quantum yield and brightness) of ThX can be used to monitor structural differences in oligomeric species, not observed via traditional ThT imaging.